Silica Sand, Activated Carbon, and Manganese Zeolite for Clean Water Filtration - HARMI TJAHJANTI, PRANTASI; Ernanda, Rico Ryan (Indonesian Journal of Cultural and Community Development, 2024)
The General Background Water is essential for human life, but many rural areas still lack access to clean drinking water that meets health standards. In Sumbergedang Village, Pandaan, local water sources are often contaminated by dissolved metals and bacteria, posing risks to community health. Current filtration methods in the area are insufficient, and limited studies explore the combined use of silica sand, activated carbon, manganese zeolite, and UV sterilization for improving rural water quality. This study aims to evaluate the performance of these filtration materials and UV sterilization in producing safe drinking water for the village. The results show that the filtration system increased the pH of the water from 7.94 to 7.98, within acceptable drinking water standards. The novelty of this research lies in the integration of filtration materials with UV sterilization to address both chemical and microbial contaminants, offering a comprehensive solution for water purification. The findings suggest that, while the system effectively improves most water quality parameters, additional treatments may be required to reduce aluminum levels to meet national drinking water standards. These results have important implications for water management in rural areas facing similar challenges. Highlihts: The study combines mangan zeolite, silica sand, and activated carbon with UV sterilization for effective water purification. Filtration and UV treatment significantly reduced turbidity, odors, and bacterial contamination in spring water. Aluminum levels exceeded permissible limits, indicating the need for further modifications to the filtration system. Keywords: Water quality, filtration, UV sterilization, rural communities, aluminum levels